Physiotherapeutic Strategies to Enhance Throwing Accuracy in Cricket Players - Touhid Hussain; Ankita Kalita; Ankur Jyoti Bora (International Journal of Orthopedic Nursing and Practices, 2024)
Background: Throwing accuracy is a crucial skill for cricket players, impacting both individual performance and team success. Physiotherapeutic strategies can enhance throwing mechanics, strength, and flexibility, leading to improved accuracy. Objectives: This study aims to outline effective physiotherapeutic interventions that optimize throwing accuracy in cricket players. Methods: A comprehensive review of current literature and practices was conducted with 3 articles found through PubMed, Google Scholar & Research Gate year range from 2019-2024. Focusing on key factors affecting throwing accuracy of all total of 120 participants, including biomechanics, muscle strength, and flexibility. Physiotherapeutic strategies were categorized into assessment, strengthening exercises, flexibility training, biomechanical training, and injury prevention. Statistics: Statistical analysis was done with Cochran’s Q test. p < 0.05 is considered statistically significant. Results: The findings highlight key strategies for enhancing throwing accuracy in cricket players. Assessing throwing mechanics and shoulder range identifies improvement areas. Strengthening the rotator cuff and core boosts power and control, while dynamic and static stretching improves shoulder mobility and Neuromuscular training showed an improved efficiency in throwing performance. Biomechanical training corrects flaws, and proper warm-up routines alongside conditioning programs reduce injury risk. Conclusion: Regular assessments and tailored exercise programs are recommended for optimal performance. Implementing targeted physiotherapeutic strategies significantly improves throwing accuracy among cricket players.
Keywords: Assessment; Performance; Throwing; biomechanics; injury prevention; neuromuscular training; strength & flexibility